Performance analysis of a space time block coded MIMO system over faded channel - Rahman, Md. Asiqur; Rahman, Abdur (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.